(untitled) (Journal of Misan Researches, 2020)
Praise is to God, from the beginning of this world to its destruction, and from the hereafter to its survival, God’s prayers came to Muhammad, the best of the people, and to his good, pure, and honorable family. That the phenomenon of contrast in the Arabic language and other languages ​​has a great importance in clarifying the meanings of words, and this is what called on researchers in this regard to delve into the depths of the sea of ​​language in search of contrasting vocabulary and its significance to its meanings, and the research on this subject was not limited to a specific generation, it has It was discussed by both the old and the modern, alike, and each of them reached what he reached in this regard, and this phenomenon (contradiction) abstained from opinions, including what was denying this phenomenon, including supporters, and others denying or endorsing but with restrictions and conditions, and some of them identified this phenomenon under certain conditions, and we In this simple paper, we review the interest of Sheikh Ahmed Reda Al-Amili (d. 1372 CE). With this phenomenon in the lexicon of the body of the language, this lexicon abounded with many linguistic phenomena and among them was the phenomenon of contradiction, and by this means the presence of two different opposing words verbally and meaning such as joy and sadness, which notes that the Sheikh has alerted them in his lexicon in a clear and clear way through the use of some expressive phrases On the opposite of them (opposite and opposite and disagreement place against). In these modest pages, I will address two requirements for studying contrast, the first: the theoretical aspect: the researcher deals with it: the concept of contrast, the position of linguists on it, and the reasons for the emergence of contrast in the language, and types of contrast. The second: the theoretical aspect: the researcher deals with analyzing some examples in the subject matter studied for the text of the body of the language.